Membrane electrode of hydrogen-oxygen fuel cell and hydrogen-oxygen fuel cell comprising membrane electrode

By adding molecular additives such as 7-ethyltheophylline to the cathode catalyst layer of the hydroxide fuel cell, the adsorption of sulfonate is suppressed, and the problem of reducing oxygen reduction reaction activity in the hydroxide fuel cell is solved, and the performance of the battery is significantly improved.

CN119812357APending Publication Date: 2025-04-11PEKING UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411881094.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the existing hydroxide fuel cells, the specific adsorption of sulfonate leads to a decrease in the oxygen reduction reaction activity of the cathode catalyst layer, resulting in severe polarization and reduced performance.

Method used

Adding specific molecular additives, such as 7-ethyltheophylline, to the cathode catalyst layer, inhibits the specific adsorption of sulfonate and improves the oxygen reduction reaction activity.

Benefits of technology

The activity of the cathode oxygen reduction reaction is significantly improved, and the membrane electrode activity and overall performance of the hydroxide fuel cell are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812357A_ABST
    Figure CN119812357A_ABST
Patent Text Reader

Abstract

The invention provides a membrane electrode of a hydrogen-oxygen fuel cell and the hydrogen-oxygen fuel cell comprising the same, the membrane electrode of the hydrogen-oxygen fuel cell comprises a proton exchange membrane, a cathode catalyst layer and an anode catalyst layer, and the proton exchange membrane is located between the cathode catalyst layer and the anode catalyst layer; the cathode catalyst layer comprises a cathode catalyst, the cathode catalyst comprises a perfluorosulfonic acid polymer, a Pt / C catalyst and a molecular additive, and the molecular additive is shown as a formula I; according to the membrane electrode of the hydrogen-oxygen fuel cell provided by the invention, the molecular additive as shown in the formula I is added into the cathode catalyst layer, so that the reaction activity of a cathode ORR can be remarkably improved, the activity of the membrane electrode of the hydrogen-oxygen fuel cell is improved, and the performance of the hydrogen-oxygen fuel cell is further improved. The invention further provides a preparation method of the membrane electrode of the hydrogen-oxygen fuel cell, and the preparation method is low in cost and convenient to operate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of fuel cells, and in particular to a membrane electrode of a hydrogen-oxygen fuel cell and a hydrogen-oxygen fuel cell comprising the membrane electrode. Background Art

[0002] Finding clean and efficient energy conversion technologies is an important measure to achieve the dual carbon goals and accelerate the global transition to a sustainable society. Hydrogen-oxygen fuel cells are electrochemical energy devices that convert chemical energy into electrical energy through electrochemical reactions. They have the advantages of high energy conversion efficiency and green sustainability, and are considered to be one of the most promising energy conversion technologies. Their emissions are only water, and they do not produce greenhouse gases or other pollutants. They have minimal impact on the environment and help reduce dependence on fossil fuels. Hydrogen-oxygen fuel cells can be used not only in automobiles, but also in many fields such as ships, drones, fixed power generation and portable power sources. With the advancement of technology and the reduction of costs, hydrogen-oxygen fuel cells are expected to occupy a more important position in the future energy structure. The membrane electrode is a key component of the proton exchange membrane hydrogen-oxygen fuel cell, including a proton exchange membrane, a cathode catalyst layer and an anode catalyst layer, a cathode gas diffusion layer and an anode gas diffusion layer. The cathode catalyst layer uses a mixed slurry of a perfluorosulfonic acid polymer (Nafion) electrolyte and a platinum-based catalyst, in which the perfluorosulfonic acid polymer electrolyte plays the role of conducting protons. However, the sulfonic acid groups in the perfluorosulfonic acid polymer electrolyte can be specifically adsorbed on the surface of platinum (Pt), resulting in the blockage of the catalytic active sites of the oxygen reduction reaction (ORR) on the Pt surface. In addition, the dense perfluorosulfonic acid polymer electrolyte coating layer will increase the gas transmission resistance. These factors will cause severe polarization of the proton exchange membrane hydrogen and oxygen fuel cells and reduce the performance of the hydrogen and oxygen fuel cells. Therefore, a suitable method is needed to inhibit the specific adsorption of sulfonic acid groups in proton exchange membrane hydrogen and oxygen fuel cells and improve the reaction activity of ORR. Summary of the invention

[0003] The purpose of this application is to provide a membrane electrode for a hydrogen-oxygen fuel cell and a hydrogen-oxygen fuel cell containing the membrane electrode, so as to improve the activity of the cathode oxygen reduction reaction, thereby improving the performance of the hydrogen-oxygen fuel cell. The specific technical solution is as follows:

[0004] The first aspect of the present application provides a membrane electrode for a hydrogen-oxygen fuel cell, which comprises a proton exchange membrane, a cathode catalyst layer and an anode catalyst layer, wherein the proton exchange membrane is located between the cathode catalyst layer and the anode catalyst layer;

[0005] The cathode catalyst layer includes a cathode catalyst, and the cathode catalyst includes a perfluorosulfonic acid polymer, a Pt / C catalyst and a molecular additive, and the molecular additive is as shown in Formula I,

[0006] Where R is C n H 2n+1 , n is an integer from 1 to 5.

[0007] The second aspect of the present application provides a method for preparing a membrane electrode for a hydrogen-oxygen fuel cell according to the first aspect of the present application, which comprises the following steps:

[0008] Preparation of the cathode catalyst layer slurry: adding a Pt / C catalyst to a first solvent to obtain a mixed solution with a Pt / C catalyst concentration of 0.8-1.2 mg / mL, adding a solution containing a perfluorosulfonic acid polymer and the molecular additive, and ultrasonicating for 0.5-1.5 h under ice bath conditions to obtain a slurry of the cathode catalyst layer; the first solvent is selected from a mixed solvent of water and isopropanol or ethanol in a volume ratio of 1:2-4;

[0009] The slurry of the anode catalyst layer is prepared by adding a Pt / C catalyst to a second solvent to obtain a mixed solution with a Pt / C catalyst concentration of 0.8-1.2 mg / mL, adding a solution containing a perfluorosulfonic acid polymer, and ultrasonicating for 0.5-1.5 h under ice bath conditions to obtain a slurry of the anode catalyst layer; the second solvent is selected from a mixed solvent of water and isopropanol or ethanol in a volume ratio of 1:2-4;

[0010] The slurry of the cathode catalyst layer is applied to one side of the proton exchange membrane, and the slurry of the anode catalyst layer is applied to the other side of the proton exchange membrane to obtain the membrane electrode of the hydrogen and oxygen fuel cell.

[0011] The third aspect of the present application provides a hydrogen-oxygen fuel cell, which includes the membrane electrode of the hydrogen-oxygen fuel cell provided in the first aspect of the present application.

[0012] The present application provides a membrane electrode of a hydrogen and oxygen fuel cell and a hydrogen and oxygen fuel cell comprising the same, wherein the membrane electrode of the hydrogen and oxygen fuel cell comprises a proton exchange membrane, a cathode catalyst layer and an anode catalyst layer, wherein the proton exchange membrane is located between the cathode catalyst layer and the anode catalyst layer; the cathode catalyst layer comprises a cathode catalyst, wherein the cathode catalyst comprises a perfluorosulfonic acid polymer, a Pt / C catalyst and a molecular additive, wherein the molecular additive is as shown in Formula I. The membrane electrode of the hydrogen and oxygen fuel cell provided by the present application, by adding a molecular additive as shown in Formula I to the cathode catalyst layer, can inhibit the specific adsorption of sulfonate in the cathode catalyst layer, significantly improve the reaction activity of the cathode ORR, thereby facilitating the improvement of the activity of the membrane electrode of the hydrogen and oxygen fuel cell, and thus improving the performance of the hydrogen and oxygen fuel cell. The present application also provides a method for preparing the membrane electrode of the hydrogen and oxygen fuel cell, which has the advantages of low cost and convenient operation. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.

[0014] Figure 1 Cyclic voltammogram of Nafion-covered pc-Pt electrode in electrolyte without molecular additives;

[0015] Figure 2 Cyclic voltammogram of pc-Pt electrode covered with Nafion in electrolyte containing molecular additives;

[0016] Figure 3 The oxygen reduction polarization curves of the Nafion-covered pc-Pt electrode measured in electrolytes containing and not containing 7-ethyltheophylline;

[0017] Figure 4 Polarization curves of membrane electrodes of hydrogen-oxygen fuel cells of Example 1 and Comparative Example 1 under hydrogen-oxygen conditions;

[0018] Figure 5 The polarization curves of the membrane electrode of the hydrogen-oxygen fuel cell of Example 1 and Comparative Example 1 under hydrogen-air conditions. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present application and the accompanying drawings to clearly and completely describe the technical solutions in the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.

[0020] The first aspect of the present application provides a membrane electrode for a hydrogen-oxygen fuel cell, which comprises a proton exchange membrane, a cathode catalyst layer and an anode catalyst layer, wherein the proton exchange membrane is located between the cathode catalyst layer and the anode catalyst layer;

[0021] The cathode catalyst layer includes a cathode catalyst, and the cathode catalyst includes a perfluorosulfonic acid polymer, a Pt / C catalyst and a molecular additive, and the molecular additive is as shown in Formula I,

[0022] Where R is C n H 2n+1 , n is an integer from 1 to 5. For example, n can be 1, 2, 3, 4, 5, or a range consisting of any two of these values.

[0023] The membrane electrode of the hydrogen-oxygen fuel cell provided in the present application, by adding a molecular additive as shown in Formula I to the cathode catalyst layer, can significantly inhibit the specific adsorption of sulfonate groups in the cathode catalyst layer, significantly improve the reaction activity of the cathode ORR, thereby facilitating the improvement of the activity of the membrane electrode of the hydrogen-oxygen fuel cell, thereby improving the energy conversion efficiency of the hydrogen-oxygen fuel cell, and improving the performance of the hydrogen-oxygen fuel cell.

[0024] In some embodiments, the Pt loading in the cathode catalyst layer is 0.1-0.15 mg / cm 2 The cathode catalyst loading is 0.2-0.4 mg / cm 2 For example, the Pt loading in the cathode catalyst layer may be 0.10 mg / cm 2 , 0.11mg / cm 2 , 0.12mg / cm 2 , 0.13mg / cm 2 , 0.14mg / cm 2 , 0.15mg / cm 2 or a range consisting of any two values ​​thereof, the cathode catalyst loading may be 0.2 mg / cm 2 , 0.25mg / cm 2 , 0.3mg / cm 2 , 0.35mg / cm 2 , 0.4mg / cm 2 Or a range consisting of any two values.

[0025] In some embodiments, in the cathode catalyst layer, the mass ratio of the molecular additive to Pt in the Pt / C catalyst is 0.08-0.12%, for example, it can be 0.08%, 0.09%, 0.10%, 0.11%, 0.12% or a range consisting of any two of these values.

[0026] In some embodiments, in the cathode catalyst layer, the mass ratio of the perfluorosulfonic acid polymer to the C in the Pt / C catalyst is 0.8-1.2, and the mass percentage of Pt in the Pt / C catalyst is 50-70%. For example, in the cathode catalyst layer, the mass ratio of the perfluorosulfonic acid polymer to the C in the Pt / C catalyst can be 0.8, 0.9, 1.0, 1.1, 1.2, or a range consisting of any two of these values, and the mass percentage of Pt in the Pt / C catalyst can be 50%, 55%, 60%, 65%, 70%, or a range consisting of any two of these values.

[0027] In some embodiments, the molecular additive is selected from at least one of 7-ethyltheophylline, 7-methyltheophylline, 7-propyltheophylline, 7-butyltheophylline, and 7-pentyltheophylline. The molecular additives of the above types are used in the present application to increase the reaction activity of cathode ORR, thereby increasing the activity of the membrane electrode of the hydrogen-oxygen fuel cell and improving the performance of the hydrogen-oxygen fuel cell.

[0028] In some embodiments, the anode catalyst layer comprises an anode catalyst, wherein the anode catalyst comprises a perfluorosulfonic acid polymer and a Pt / C catalyst; the Pt loading in the anode catalyst layer is 0.04-0.08 mg / cm 2 The loading of the anode catalyst is 0.1-0.18 mg / cm 2 For example, the Pt loading in the anode catalyst layer may be 0.04 mg / cm 2 , 0.05mg / cm 2 , 0.06mg / cm 2 , 0.07mg / cm 2 , 0.08mg / cm 2 or a range consisting of any two values ​​thereof, the loading amount of the anode catalyst can be 0.10 mg / cm 2 , 0.12mg / cm 2 , 0.14mg / cm 2 , 0.15mg / cm 2 , 0.16mg / cm 2 、0.18mg / cm 2 Or a range consisting of any two values.

[0029] In some embodiments, in the anode catalyst layer, the mass ratio of the perfluorosulfonic acid polymer to the C in the Pt / C catalyst is 0.8-1.2, and the mass percentage of Pt in the Pt / C catalyst is 50-70%. For example, in the anode catalyst layer, the mass ratio of the perfluorosulfonic acid polymer to the C in the Pt / C catalyst can be 0.8, 0.9, 1.0, 1.1, 1.2, or a range consisting of any two of these values, and the mass percentage of Pt in the Pt / C catalyst can be 50%, 55%, 60%, 65%, 70%, or a range consisting of any two of these values.

[0030] In some embodiments, the proton exchange membrane is a Nafion proton exchange membrane; the Nafion proton exchange membrane can be a Nafion proton exchange membrane that can be purchased on the market. The present application does not specifically limit its source as long as the purpose of the present application can be achieved.

[0031] The present application has no particular limitation on the preparation method of the molecular additive as shown in Formula I, as long as the purpose of the present application can be achieved; illustratively, the preparation steps of the molecular additive as shown in Formula I include:

[0032] Theophylline and K2CO3 are added to N,N-dimethylformamide (DMF). Alkyl iodide RI is then added, and the molar ratio of theophylline to RI is 1:1.4-1.6. The reaction mixture is stirred at 40-50°C for 10-14 h. After cooling to room temperature, H2O is added. Extract with CH2Cl2, and the resulting organic phase is dried to obtain a crude product. The crude product is recrystallized and dried to obtain a molecular additive as shown in Formula I. The reaction equation is as follows:

[0033] Where R is C n H 2n+1 , n is an integer of 1 to 6. The present invention can prepare a high-purity theophylline derivative as shown in formula I through organic synthesis and post-recrystallization treatment.

[0034] The second aspect of the present application provides a method for preparing a membrane electrode for a hydrogen-oxygen fuel cell according to the first aspect of the present application, which comprises the following steps:

[0035] Preparation of the cathode catalyst layer slurry: adding a Pt / C catalyst to a first solvent to obtain a mixed solution with a Pt / C catalyst concentration of 0.8-1.2 mg / mL, adding a solution containing a perfluorosulfonic acid polymer and the molecular additive, and ultrasonicating for 0.5-1.5 h under ice bath conditions to obtain a slurry of the cathode catalyst layer; the first solvent is selected from a mixed solvent of water and isopropanol or ethanol in a volume ratio of 1:2-4;

[0036] The slurry of the anode catalyst layer is prepared by adding a Pt / C catalyst to a second solvent to obtain a mixed solution with a Pt / C catalyst concentration of 0.8-1.2 mg / mL, adding a solution containing a perfluorosulfonic acid polymer, and ultrasonicating for 0.5-1.5 h under ice bath conditions to obtain a slurry of the anode catalyst layer; the second solvent is selected from a mixed solvent of water and isopropanol or ethanol in a volume ratio of 1:2-4;

[0037] The slurry of the cathode catalyst layer is applied to one side of the proton exchange membrane, and the slurry of the anode catalyst layer is applied to the other side of the proton exchange membrane to obtain the membrane electrode of the hydrogen and oxygen fuel cell.

[0038] In the present application, in a mixed solvent of water and isopropanol, the volume ratio of water and isopropanol can be, for example, 1:2, 1:3, 1:4 or a range consisting of any two of the values ​​therein. In a mixed solvent of water and ethanol, the volume ratio of water and ethanol can be, for example, 1:2, 1:3, 1:4 or a range consisting of any two of the values ​​therein. The Pt / C catalyst concentration can be 0.8 mg / mL, 0.9 mg / mL, 1.0 mg / mL, 1.1 mg / mL, 1.2 mg / mL or a range consisting of any two of the values ​​therein. The time of ultrasound under ice bath conditions can be 0.5 h, 1 h, 1.5 h or a range consisting of any two of the values ​​therein. In the present application, the ice bath conditions include an ice bath temperature of 0-5°C.

[0039] The method for preparing the membrane electrode of the hydrogen-oxygen fuel cell provided in the present application has the advantages of low cost and convenient operation, and is conducive to obtaining a hydrogen-oxygen fuel cell with high energy conversion efficiency.

[0040] In some embodiments, the mass percentage of the perfluorosulfonic acid polymer in the solution containing the perfluorosulfonic acid polymer is 5-10%. For example, the mass percentage of the perfluorosulfonic acid polymer in the solution containing the perfluorosulfonic acid polymer can be 5%, 6%, 7%, 8%, 9%, 10%, or a range consisting of any two of these values. The source of the solution containing the perfluorosulfonic acid polymer is not particularly limited in the present application, as long as the purpose of the present application can be achieved, for example, it can be obtained by purchasing a 5-10wt% Nafion solution from the market.

[0041] The third aspect of the present application provides a hydrogen-oxygen fuel cell, which includes the membrane electrode of the hydrogen-oxygen fuel cell provided in the first aspect of the present application, or the membrane electrode of the hydrogen-oxygen fuel cell prepared according to the preparation method of the membrane electrode of the hydrogen-oxygen fuel cell provided in the second aspect of the present application. The hydrogen-oxygen fuel cell provided in the present application has a high energy conversion efficiency.

[0042] Example

[0043] Hereinafter, embodiments and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations are performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are weight references. The experimental materials used in the following embodiments are conventional materials and can be purchased commercially unless otherwise specified.

[0044] Preparation of molecular additive 7-ethyltheophylline:

[0045] Theophylline (1.8 g) and anhydrous K2CO3 (2.1 g) were added to 5 mL of DMF. CH3CH2I (1.5 equiv.) was then added dropwise. The reaction mixture was stirred at 45 °C for 12 h. After cooling to room temperature, 20 mL of H2O was added. The resulting mixture was extracted three times with CH2Cl2 and the resulting organic phase was dried over MgSO4. The organic liquid was dried by rotary evaporation to obtain a crude product. The crude product was recrystallized from a hexane / ethyl acetate mixed solvent and the resulting solid was dried under vacuum to obtain 7-ethyltheophylline with a purity of >99%. The reaction equation is as follows:

[0046] Testing of the effect of molecular additives on the oxygen reduction reaction activity of Pt electrodes:

[0047] The Nafion solution (5wt%, Sigma-Aldrich) was diluted 1000 times, and 5 μL of the diluted Nafion solution was added dropwise on the surface of polycrystalline platinum. After natural drying, a polycrystalline Pt electrode (pc-Pt electrode) covered with Nafion was obtained.

[0048] Argon was introduced into 0.1 mol / L HClO4 electrolyte without 7-ethyltheophylline to fully saturate it. The cyclic voltammetry test of the Nafion-covered pc-Pt electrode was performed. The electrode potential was cyclically scanned between 0.05 V and 1 V at a rate of 50 mV / s. The reference electrode was a reversible hydrogen electrode (platinum wire, RHE) and the counter electrode was a platinum wire. The cyclic voltammogram of the Nafion-covered pc-Pt electrode in the electrolyte without molecular additives was obtained as shown in the figure. Figure 1 As shown, the positions at 0.18 V and 0.30 V correspond to the specific adsorption peaks of sulfonate.

[0049] The molecular additive 7-ethyltheophylline was added to a 0.1 mol / L HClO4 solution to prepare a solution containing 1×10 -6 The pc-Pt electrode covered with Nafion was immersed in the electrolyte saturated with argon gas for cyclic voltammetry test. The electrode potential was cyclically scanned between 0.05V and 1 V at a rate of 50 mV / s. The reference electrode was a reversible hydrogen electrode and the counter electrode was a platinum wire. The cyclic voltammogram of the pc-Pt electrode covered with Nafion in the electrolyte containing the molecular additive is shown in Figure 2. Figure 2 As shown in Figure 2, during the potential cycle scan, 7-ethyltheophylline gradually deposited on the Pt electrode surface and then reached a stable coverage, which was consistent with the Figure 1 compared to, Figure 2It can be seen that the adsorption peak of sulfonate is reduced, and the areas of hydrogen adsorption region (Hupd region) and hydrogen and oxygen adsorption and desorption region (OH region) are also reduced, indicating that the molecular additive of the present application can inhibit the specific adsorption of sulfonate.

[0050] Oxygen was introduced into the electrolyte containing and not containing 7-ethyltheophylline to fully saturate it. The rotation speed of the Nafion-covered pc-Pt electrode was adjusted to 1600 rpm. The electrode potential was scanned from 0.1 V to 1.02 V at a rate of 20 mV / s. The oxygen reduction polarization curve was recorded, wherein the reference electrode was a reversible hydrogen electrode and the counter electrode was a platinum wire. The oxygen reduction polarization curves of the Nafion-covered pc-Pt electrode measured in the electrolyte containing and not containing 7-ethyltheophylline are shown in FIG. Figure 3 As shown, it can be seen that the activity of oxygen reduction reaction is significantly improved in the electrolyte containing theophylline derivative molecular additives.

[0051] Example 1

[0052] Preparation of cathode catalyst layer slurry: Pt / C catalyst containing 60wt% Pt was dispersed in a mixed solvent of water and isopropanol with a volume ratio of water to isopropanol of 1:3 to obtain a mixed solution with a Pt / C catalyst concentration of 1mg / mL, and Nafion solution (5wt%) was added so that the mass ratio of Nafion to C in the Pt / C catalyst was 1.0. At the same time, a molecular additive 7-ethyltheophylline was added with a mass ratio of the molecular additive to Pt in the Pt / C catalyst of 0.1%. The mixture was ultrasonicated in an ice bath for 1h to obtain a uniformly dispersed cathode catalyst layer slurry.

[0053] Preparation of anode catalyst layer slurry: Pt / C catalyst containing 60 wt% Pt was dispersed in a mixed solvent of water and isopropanol with a volume ratio of water to isopropanol of 1:3 to obtain a mixed solution with a Pt / C catalyst concentration of 1 mg / mL. Nafion solution (5 wt%) was added so that the mass ratio of Nafion to the mass of C in the Pt / C catalyst was 1.0. Ultrasonic treatment was performed in an ice bath for 1 h to obtain a uniformly dispersed slurry of the anode catalyst layer.

[0054] The cathode catalyst layer slurry prepared above was sprayed onto one side of a 4 cm × 4 cm Nafion NC700 proton exchange membrane by an ultrasonic spraying device and dried. The cathode catalyst layer covered an area of ​​2.2 cm × 2.3 cm, about 5 cm 2 ; The anode catalyst layer slurry prepared above was sprayed on the other side of the Nafion NC700 proton exchange membrane in the same area as the cathode catalyst layer by an ultrasonic spraying device and dried, that is, the area covered by the anode catalyst layer was also 2.2 cm × 2.3 cm, about 5 cm 2The catalyst coating membrane was obtained. The Pt loading in the cathode catalyst layer was calculated by weighing on a balance to be 0.12 mg / cm 2 The cathode catalyst loading including Nafion, Pt / C catalyst and molecular additives is 0.28 mg / cm 2 ; The Pt loading in the anode catalyst layer is 0.06 mg / cm 2 The anode catalyst loading of Nafion and Pt / C catalyst was 0.14 mg / cm 2 .

[0055] Use commercial 5cm 2 Hydrogen and oxygen fuel cell test fixture, size 10.5cm×10.5cm. Thickness 0.1mm, center leave 5cm 2 A polytetrafluoroethylene (PTFE) gasket with a square hole (2.2 cm × 2.3 cm) was placed on the anode graphite plate (7.5 cm × 7.5 cm) and a 5 cm 2 Sigracet 28BC carbon paper of size (2.2cm×2.3cm), with the microporous layer of the carbon paper facing up. Place the above-prepared catalyst-coated membrane on the carbon paper, with the anode catalyst layer facing down and spread out flat. Cover it with another PTFE gasket with a center hole and a thickness of 0.2mm, and place another Sigracet 28BC carbon paper in the center, with the microporous layer of the carbon paper facing down. The two carbon papers overlap the effective area on the catalyst-coated membrane, and the size of the carbon paper is not larger than the central square hole of the PTFE gasket. Then cover it with a cathode graphite plate (7.5cm×7.5cm). Use a torque wrench to control the torque of the pressure screw to 4 N·m to obtain the membrane electrode of the hydrogen and oxygen fuel cell.

[0056] Comparative Example 1

[0057] The process is the same as Example 1 except that no molecular additive is added in the preparation of the slurry for the cathode catalyst layer.

[0058] Performance test of membrane electrode of hydrogen and oxygen fuel cell:

[0059] The membrane electrode of the hydrogen and oxygen fuel cell was tested under hydrogen-oxygen and hydrogen-air conditions using a fuel cell workstation. The test was carried out at 80°C, with a relative humidity of 100%, a hydrogen and air pressure of 100kPa back pressure (200kPa absolute pressure), a hydrogen flow rate of 0.5L / min, an oxygen flow rate of 0.5L / min, and an air flow rate of 0.5L / min. The test was carried out in voltage scanning mode, and the control voltage was increased from 0.35V to 0.95V in steps of 50mV every 30s. The output current and power were obtained by testing. The current density and power density were calculated based on current density = current / area and power density = power / area, and the polarization curves of the membrane electrode of the hydrogen and oxygen fuel cell of Example 1 and Comparative Example 1 under hydrogen-oxygen conditions were obtained as shown below. Figure 4 As shown, the polarization curves of the membrane electrode of the hydrogen-oxygen fuel cell of Example 1 and Comparative Example 1 under hydrogen-air conditions are as follows Figure 5 shown.

[0060] according to Figure 4 and Figure 5 Under hydrogen-oxygen conditions, the maximum power density of the membrane electrode of the hydrogen-oxygen fuel cell of Example 1 is 2.01 W·cm -2 , which is significantly higher than the maximum power density of 1.40 W·cm of the membrane electrode of the hydrogen-oxygen fuel cell in Comparative Example 1. -2 Under hydrogen-air conditions, the maximum power density of the membrane electrode of the hydrogen-oxygen fuel cell in Example 1 is 0.731 W·cm -2 , which is significantly higher than the maximum power density of the membrane electrode of the hydrogen-oxygen fuel cell in Comparative Example 1 (0.644 W·cm -2 It can be seen that the membrane electrode activity of the hydrogen-oxygen fuel cell containing the molecular additive of the present application is significantly improved. It can be known that the addition of the molecular additive shown in Formula I in the present application can increase the activity of the cathode oxygen reduction reaction, thereby improving the energy conversion efficiency of the hydrogen-oxygen fuel cell and improving the performance of the hydrogen-oxygen fuel cell.

[0061] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.

[0062] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A membrane electrode for a hydrogen-oxygen fuel cell, comprising a proton exchange membrane, a cathode catalyst layer and an anode catalyst layer, wherein the proton exchange membrane is located between the cathode catalyst layer and the anode catalyst layer; The cathode catalyst layer includes a cathode catalyst, and the cathode catalyst includes a perfluorosulfonic acid polymer, a Pt / C catalyst and a molecular additive, and the molecular additive is as shown in Formula I, Where R is C n H 2n+1 , n is an integer from 1 to 5.

2. The membrane electrode for hydrogen and oxygen fuel cells according to claim 1, wherein: The Pt loading in the cathode catalyst layer is 0.1-0.15 mg / cm 2 The cathode catalyst loading is 0.2-0.4 mg / cm 2 .

3. The membrane electrode for hydrogen and oxygen fuel cell according to claim 1, wherein: In the cathode catalyst layer, the mass ratio of the molecular additive to Pt in the Pt / C catalyst is 0.08-0.12%.

4. The membrane electrode for hydrogen and oxygen fuel cell according to claim 1, wherein: In the cathode catalyst layer, the mass ratio of the perfluorosulfonic acid polymer to C in the Pt / C catalyst is 0.8-1.2, and the mass percentage of Pt in the Pt / C catalyst is 50-70%.

5. The membrane electrode for hydrogen and oxygen fuel cell according to claim 1, wherein: The molecular additive is selected from at least one of 7-ethyltheophylline, 7-methyltheophylline, 7-propyltheophylline, 7-butyltheophylline and 7-pentyltheophylline.

6. The membrane electrode for a hydrogen-oxygen fuel cell according to any one of claims 1 to 5, wherein: The anode catalyst layer comprises an anode catalyst, and the anode catalyst comprises a perfluorosulfonic acid polymer and a Pt / C catalyst; the Pt loading in the anode catalyst layer is 0.04-0.08 mg / cm 2 The loading of the anode catalyst is 0.1-0.18 mg / cm 2 .

7. The membrane electrode for hydrogen and oxygen fuel cell according to claim 6, wherein: In the anode catalyst layer, the mass ratio of the perfluorosulfonic acid polymer to C in the Pt / C catalyst is 0.8-1.2, and the mass percentage of Pt in the Pt / C catalyst is 50-70%.

8. A method for preparing a membrane electrode for a hydrogen-oxygen fuel cell according to any one of claims 1 to 7, comprising the following steps: Preparation of the cathode catalyst layer slurry: adding a Pt / C catalyst to a first solvent to obtain a mixed solution with a Pt / C catalyst concentration of 0.8-1.2 mg / mL, adding a solution containing a perfluorosulfonic acid polymer and the molecular additive, and ultrasonicating for 0.5-1.5 h under ice bath conditions to obtain a slurry of the cathode catalyst layer; the first solvent is selected from a mixed solvent of water and isopropanol or ethanol in a volume ratio of 1:2-4; The slurry of the anode catalyst layer is prepared by adding a Pt / C catalyst to a second solvent to obtain a mixed solution with a Pt / C catalyst concentration of 0.8-1.2 mg / mL, adding a solution containing a perfluorosulfonic acid polymer, and ultrasonicating for 0.5-1.5 h under ice bath conditions to obtain a slurry of the anode catalyst layer; the second solvent is selected from a mixed solvent of water and isopropanol or ethanol in a volume ratio of 1:2-4; The slurry of the cathode catalyst layer is applied to one side of the proton exchange membrane, and the slurry of the anode catalyst layer is applied to the other side of the proton exchange membrane to obtain the membrane electrode of the hydrogen and oxygen fuel cell.

9. The preparation method according to claim 8, wherein: The mass percentage of the perfluorosulfonic acid polymer in the perfluorosulfonic acid polymer-containing solution is 5-10%.

10. A hydrogen-oxygen fuel cell comprising the membrane electrode of any one of claims 1 to 7.

Citation Information

Patent Citations

  • Anode catalyst layer slurry and preparation method thereof

    CN113745551A

  • Fuel cell catalyst layer and preparation method thereof

    CN115050970A

  • Fuel cell catalyst layer, preparation method thereof and membrane electrode

    CN117410505A

  • Membrane electrode of fuel cell and preparation method of membrane electrode

    CN117810498A

  • Compositions for activating oxygen reduction catalysts, electrodes for fuel cells, fuel cells, and methods for activating oxygen reduction catalysts

    JP2024125079A